Lecturers' readiness for EMI in Malaysia higher education. - Yueh Yea Lo; Juliana Othman (PLoS ONE)
The current study aims to examine lecturer readiness for English Medium Instruction (EMI) in higher educational institutions and the contextual influences of gender, age, academic qualification, teaching experience, EMI course teaching involvement, and EMI training. A quantitative research design was employed, and a survey questionnaire was completed by 227 lecturers (out of 250 invited participants) from private universities in Klang Valley, Malaysia to gauge self-ratings of personal knowledge, skills, abilities, and attitudes in educating EMI courses. The collected data were subsequently analysed via the Statistical Package for Social Sciences (SPSS) version 27.0 software before revealing the findings from the inferential statistics of the t-test and one-way analysis of variance (ANOVA) on lecturers' gender, age, academic qualification, teaching experience, EMI course teaching involvement, and EMI training. Resultantly, the important role of lecturers' knowledge, understanding, skills, abilities, and attitudes was highlighted to further enhance intercultural communicative competence in managing the increasingly diversified student body in EMI classrooms.